Anti-Alzheimer’s Studies on β-Sitosterol Isolated from Polygonum hydropiper L. - Ayaz, Muhammad; Junaid, Muhammad; Ullah, Farhat; Subhan, Fazal; Sadiq, Abdul; Ali, Gowhar; Ovais, Muhammad; Shahid, Muhammad; Ahmad, Ashfaq; Wadood, Abdul; El-Shazly, Mohamed; Ahmad, Nisar; et al. (Frontiers in Pharmacology, 2017)
The family Polygonaceae is known for its traditional use in the management of various neurological disorders including Alzheimer disease (AD). In search of new anti-AD drugs, β-sitosterol isolated from Polygonum hydropiper was subjected to in vitro, in vivo, behavioral and molecular docking studies to confirm its possibility as a potential anti-Alzheimer’s agent. The in vitro AChE, BChE inhibitory potentials of β-sitosterol were investigated following Ellman's assay. The antioxidant activity was tested using DPPH, ABTS and H2O2 assays. Behavioral studies were performed on a sub-strain of transgenic mice using shallow water maze (SWM), Y-maze and balance beam tests. β-sitosterol was tested for in vivo inhibitory potentials against cholinesterase's and free radicals in the frontal cortex (FC) and hippocampus (HC). The molecular docking study was performed to predict the binding mode of β-sitosterol in the active sites of AChE and BChE as inhibitor. Considerable in vitro and in vivo cholinesterase inhibitory effects were observed in the β-sitosterol treated groups. β-sitosterol exhibited an IC50 value of 55 and 50 µg/ml against AChE and BChE respectively. Whereas, the activity of these enzymes were significantly low in FC and HC homogenates of transgenic animals. Molecular docking studies also support the binding of β-sitosterol with the target enzyme and further support the in vitro and in vivo results. In the antioxidant assays, the IC50 values were observed as 140, 120 and 280 µg/ml in the DPPH, ABTS and H2O2 assays respectively. The free radicals load in the brain tissues was significantly declined in the β-sitosterol treated animals as compared to the transgenic-saline treated groups. In the memory assessment and coordination tasks including SWM, Y-maze and balance beam tests, β-sitosterol treated transgenic animals showed gradual improvement in working memory, spontaneous alternation behavior and motor coordination. These results conclude that β-sitosterol is a potential compound for the management of memory deficit disorders like AD.